White House : - Goldberg, Vicki. (Little, Brown and Co, 2011)
White House Life over the past 200 years. Witness multiple refurbishments to the house, media coverage and popular photography of the White House, and photos of its illustrious inhabitants, visitors, and even pets and illustrations. Accompanying the photographs is an incisive, informative text by renowned critic Vicki Goldberg.